Temporal dynamics of abundant and rare microbial communities in fermented grains during Chinese light-aroma Baijiu fermentation - Lin, Bin; Jiang, Wei; Tang, Jie; Li, Qun; Li, Rui; Zhu, Liping; Zhang, Fan; Yang, Shengzhi; Yang, Qiang; Chen, Shenxi (Frontiers in Microbiology, 2025)
The Chinese Baijiu fermentation process involves a complex multi-species microbial community, including both abundant and rare taxa. However, the rare and abundant microbes in fermented grains during Baijiu fermentation are poorly understood. In this study, we investigated the succession of abundant and rare microbial communities during Chinese light-aroma Baijiu (LAB) fermentation using the Illumina MiSeq and PacBio sequencing platforms. Our results showed that a total of 78 rare genera and 24 abundant genera were identified in the bacterial community. In comparison, 135 rare genera, 30 abundant genera, and two moderate genera were detected in the fungal community during the LAB fermentation. Abundant and rare microbial taxa showed significant differences in microbial diversity and taxonomic composition during two consecutive fermentation stages. At the later stage of grain fermentation, Lactobacillus, Saccharomyces, and Condenascus emerged as the dominant abundant genera. Unlike bacterial rare taxa (BRT), fungal dominant rare genera, including Cladosporium, Saitozyma, Russula, Alternaria, Oidiodendron, and Chaetomium, had an increasing trend throughout the fermentation process. Molecular ecological network analysis indicated that rare taxa, which accounted for more than 50% of keystone operational taxonomic units (OTUs), played a key role in maintaining the microbial community structure in fermented grain, and the bacterial network showed lower complexity than the fungal network at the late stage of grain fermentation. Moreover, the assembly of rare and abundant microbial communities was governed by stochastic processes. This study provides new insights into understanding the dynamic succession of abundant and rare taxa during LAB fermentation, thereby improving the quality and controllability of Baijiu production.